Polish and English Discourses on the History of Medieval Italy: A Polysystem Study - Marcinkiewicz, Paweł (Perspektywy Kultury, 2023)
The article deals with the problem of polysystem differences between Polish and English historical text dealing with Middle Ages. In the Polish literary tradition, the Renaissance poetics of translation favored free adaptations, totally independent of the originals. The British tradition of translation, codified at the end of the eighteenth century, did not allow paraphrase. On the contrary, translation should give a full transcript of the idea of the original text, while the style and manner of rendering should have the same character as in the original. As for the rhetoric of science, in the Polish language, it was first shaped by literary models of highly declensional Latin and then French models of purple prose. In the English language, scientific diction was based on inherent Germanic and Norman syntax-oriented models and openness to foreign patterns which was valued as a resistance against smooth reading and straightforward interpretations. The article analyses Henryk Samsonowicz’s introduction to Rozkwit średniowiecznej Europy [The Heyday of Medieval Europe] (2001) as well as the Polish translation of Chris Wickham’s Medieval Rome. Stability and Crisis of the City, 900–1150 (2015). The conclusion is that Polish and English scientific texts – not only those treating about Italy in the Middle Ages – belong to different genres. While Polish authors try to create linguistically transparent, smooth, and stylized essays belonging to belles-lettres, their English colleagues seem to be down-to-earth and precise, consciously preserving traces of cultural (Italian/ Roman) foreignness.